MUSIC INTERACTION AND MOVEMENT IN JAVANESE DANCE: CASE STUDY ON BEKSAN BEDHAYA GANDAKUSUMA MANGKUNEGARAN STYLE - Sriyadi Sriyadi (Universitas Gadjah Mada, 2023)
The music and movement patterns in Javanese dance occupy a significant position, which both of them have an integral relationship in forming the construction of a dance. It represented through the relationship between dance music and the technique of composing and executing movement patterns. This article examines the integral relationship between dance music and movement patterns to determine the importance of these two components in the formation of Javanese dance . The case study chosen to show this integral relationship is the Mangkunegaran style of Bêdhåyå Gåndåkusumå dance. The bêdhåyå dance is the result of absorption carried out by K.G.P.A.A. Mangkunegara VII (1916-1944) through a learning system at Kridha Beksa Wirama Yogyakarta. This research uses an ethnochoreological approach in the form of qualitative research. The position of dance as a multidimensional object in the ethnochoreological approach is seen through the choreographic dimension, which is expected to be able to describe the integral relationship between dance music and movement patterns in forming a Javanese dance construction. Data collection techniques were carried out through participatory observation, literature study, and interviews. Based on research results in the Bêdhåyå Gåndåkusumå dance, the technique for composing movement patterns always pay attention to the instrument colotomy of dance music. Gêndhing rhythms have contributed to realizing the aesthetic stability of the execution of a series of movements.